The Impact of Ethical Leadership on Employee Engagement Through Job Insecurity - Dedi Kurniawan; Pras Rendi; Nunung Ayu Sofiati; Rama Chandra (GoAcademica Research & Publishing, 2026)
This research investigates how ethical leadership shapes employee engagement, with job insecurity examined as a possible mediating mechanism at Bank Syariah Indonesia KC Jakarta Fatmawati 2. 172 employees who were chosen by probability sampling were surveyed for the study using a quantitative explanatory design. Structured questionnaires were used to collect the data, and SEM-PLS was used for analysis. Sound instruments are confirmed by the measurement model, which shows that all constructs meet reliability, discriminant validity, and convergent validity requirements. Structural results show ethical leadership exerts a strong, positive, and significant direct effect on employee engagement, implying that leaders who act with integrity, fairness, and transparency strengthen employees’ vigor, dedication, and involvement at work. In contrast, ethical leadership does not significantly predict job insecurity, and job insecurity does not significantly predict employee engagement. Nonetheless, bootstrapped mediation testing reveals a significant indirect effect of ethical leadership on engagement through job insecurity, consistent with an indirect-only mediation pattern. Overall, ethical leadership emerges as the primary driver of employee engagement, while job insecurity contributes a secondary, limited mediating pathway, underscoring the importance of reinforcing ethical leadership practices.